Toxicology of chemical mixtures : case studies, mechanisms, and novel approaches - Yang, Raymond Shih-hsien, 1940- (Academic Press, 1994)
Although toxicologic studies in the laboratory often focus on a single chemical, in the larger world, mixtures of chemicals are routinely encountered. Toxicology of Chemical Mixtures examines the mechanisms of interactions and health effects stemming from chemical mixtures in the environment. Toxicologists, pharmacologists, environmental scientists, and professionals involved in environmental clean-ups will benefit from its content. Emphasis is on low-level, long-term exposure.